Les premières institutions bancaires de la rue Masson - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Banque Canadienne nationale; Banque d'Hochelaga; Banque de Montréal; Banques

Marion Nelson Crawford, la partenaire du notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Crawford; Alexander

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Dictionnaire historique des gens du livre au Québec - Aubin, Paul; Luneau, Marie-Pier; Vincent, Josée (Les Presses de l'Université de Montréal, 2022)
Keywords: Imprimerie

At St Anne's Market (1834-1844). All Kinds of Products, All Kinds of Meetings - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n84 Translators: _:n62458
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

St Anne's Market. A Long-Awaited Project - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n73 Translators: _:n62480
Keywords: Marchés; Sainte-Anne (marché)

Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2022)
Translators: _:n461 Translators: _:n62043
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

For Our Collective Heritage. Nothing Is Loss Forever - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n199 Translators: _:n62269
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n27 Translators: _:n62469
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
issued: 2022-21-00
Keywords: Saint-Jean-Baptiste (village); Villages

L'intendance sociale du capital : philanthropie d'entreprise et hôpitaux généraux montréalais, 1880-1915 - Dubreuil, Anne-Marie (Université du Québec à Montréal, 2022)
Keywords: Hôpital Notre-Dame; Hôpitaux; Montreal General Hospital; Philanthropie; Royal Victoria Hospital

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Soundways Montreal to La Cloche - Laxer, Daniel Robert (Listening to the Fur Trade. Soundways and Music in the British North American Fur Trade, 1760-1840, 2022)
Keywords: Autochtones; Fourrure; Marchands

“Perfect Dry Plates for Canada”: Gelatine Dry-Plate Manufacturing in Canada in the Late Nineteenth Century - Perry, Shannon (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Notman; William; Photographie; Publicité

DUPUIS, JOSEPH-NARCISSE (Dictionnaire biographique du Canada, 2022)

Two Commemorative Pitchers, or the End of an Era. 1846. Repeal of the Corn Laws - Pothier, Louise (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n188 Translators: _:n62336
Keywords: Archéologie; Céréales; Incendies; Marchands; Mouvement annexionniste; Parlement; Prix

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n62 Translators: _:n62435
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n95 Translators: _:n62402
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Montréal, Hospitable Capital City - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n139 Translators: _:n62391
Keywords: Hôtellerie; Marchés

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n38 Translators: _:n62447
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-21-00
Keywords: Chemins de fer; Paysages

Sir Hormisdas Laporte: Homme d'affaires et maire de Montréal (1850-1934) - Saint-Pierre, Marjolaine (Septentrion, 2022)
Keywords: Maires; Philanthropie

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-23-00
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-24-00
Keywords: Routes; Saint-Laurent (rue)

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)